2012
DOI: 10.1096/fj.11-194423
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of RanBP9 in integrin‐dependent focal adhesion signaling and assembly

Abstract: Accumulation of the amyloid β (Aβ) peptide derived from the amyloid precursor protein (APP) plays a central role in the pathogenesis of Alzheimer's disease (AD). We previously reported that the scaffolding protein RanBP9 is markedly increased in AD brains and promotes Aβ generation by scaffolding APP/BACE1/LRP complexes together and accelerating APP endocytosis. Because APP, LRP, and RanBP9 all physically interact with β-integrins, we investigated whether RanBP9 alters integrin-dependent cell adhesion and foca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…25 We have previously shown that RanBP9 accelerates APP, LRP, and b1-integrin endocytosis, simultaneously leading to increased Ab generation in vitro and in vivo 6,7 and disruption of focal adhesions. 9 As such, our observation that RanBP9 activates/dephosphorylates cofilin is consistent with the known role of the integrin-LIMK pathway in the inactivation/phosphorylation of cofilin, although the Slingshot pathway cannot be ruled out. Therefore, we propose that disruption of cell adhesive processes via deregulation of integrin-dependent focal adhesions and activation of cofilin underlie both Ab and RanBP9-induced increase in the vulnerability of neurons to undergo neuritic dysfunction, synapse loss, and mitochondria-mediated apoptotic process (Figure 8).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…25 We have previously shown that RanBP9 accelerates APP, LRP, and b1-integrin endocytosis, simultaneously leading to increased Ab generation in vitro and in vivo 6,7 and disruption of focal adhesions. 9 As such, our observation that RanBP9 activates/dephosphorylates cofilin is consistent with the known role of the integrin-LIMK pathway in the inactivation/phosphorylation of cofilin, although the Slingshot pathway cannot be ruled out. Therefore, we propose that disruption of cell adhesive processes via deregulation of integrin-dependent focal adhesions and activation of cofilin underlie both Ab and RanBP9-induced increase in the vulnerability of neurons to undergo neuritic dysfunction, synapse loss, and mitochondria-mediated apoptotic process (Figure 8).…”
Section: Discussionsupporting
confidence: 88%
“…8 In addition to promoting Ab generation by accelerating APP endocytosis, RanBP9 also potently disrupts integrin-dependent focal adhesion signaling and assembly by accelerating b1-integrin and LRP endocytosis. 9 In this study, we found that RanBP9 levels are increased not only in brains of AD patients but also in APP transgenic mice. Increased RanBP9 expression significantly induces gliosis, neurodegeneration, synapse loss, and spatial memory deficits.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…We thus cotransfected EGFP-Gasz with its protein partners and examined the effects on Gasz localization. RanBP9 is a scaffold protein that has been reported to function as a signaling platform and interact with a variety of partners including nuclear receptors, cytoplasmic kinases, receptor tyrosine kinases, and centrosome-localized proteins [20, 21]. When transfected into HeLa cells, we observed cytoplasmic and microtubular-appearing patterns of distribution, but no effect on the mitochondrial localization of Gasz was noted (Figure 4(a)).…”
Section: Resultsmentioning
confidence: 91%
“…Importantly, COPS5 not only binds RanBP9, BACE1, LRP, and APP (27), which are all known to increase A␤ generation by targeting APP to lipid rafts, but we and others have shown previously that COPS5 binds LFA-1 (41,42), and LFA-1, in turn, binds LRP (43). Interestingly, we also showed that RanBP9 increases endocytosis of LFA-1, LRP, and APP, thereby regulating cell adhesion and A␤ generation (44). By increasing endocytosis of LFA-1 and other integrins that are known to transduce synaptic plasticity signals, the COPS5/RanBP9 pathway may indirectly regulate synaptic alterations and behavioral deficits.…”
Section: Volume 290 • Number 14 • April 3 2015mentioning
confidence: 51%